Response of Morphological and Physiological Characteristics of 4 Flood- tolerant Sugarcane (Saccharum Officinarum L.) Cultivars to ZA (Zwavelzuur Ammoniac) fertilizer application in Jember and Bondowoso - Sholeh Avivi; Cacuk Purnomo; Ayu Puspita Arum; Sugeng Winarso; Sri Hartatik (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2019)
The business expansion of sugarcane can be done using marginal land, such as wet land. This study attempted to get the right doses of ZA fertilizer applied to several sugarcane cultivars, which are tolerant to flooding in two different locations. The research was carried out in Jubung Agrotechnopark garden, University of Jember and seed gardens of Dewisri Bondowoso, from November 2015 to November 2016. The experiment was arranged in factorial randomized complete block design. The first factor was the doses of ZA fertilizer, consisting of 3 levels of treatment, i.e. 0 kg.ha-1 (without ZA fertilizer), 500 kg.ha-1 and 1000 kg.ha-1. The second factor was 4 sugarcane cultivars, consisting of flood-tolerant sugarcane cultivars from 2014 screening result, i.e. PSJT 941, Bulu Lawang, PS 865 and Kidang Kencana. The results showed that the application of ZA fertilizer at 1000 kg.ha-1 affected the height of stems, the number of tillers, diameter of the stem and the number of segments. Meanwhile, the application of ZA fertilizer at 500 kg.ha-1 affected the number of leaves, fresh weight of shoots, dry weight of shoots, fresh weight of roots, dry weight of roots, brix content, and the content of sucrose and reducing sugar. Flood-tolerant sugarcane cultivars are shown by the highest brix and sucrose fertilizer, observed in PS 865, Bulu Lawang, PSJT 941, and Kidang Kencana, sequentially. The highest content of reducing sugar was found in PSJT 941, PS 865, Kidang Kencana, and Bulu Lawang, successively.